PUSAT KESEHATAN MENTAL BERBASIS INKLUSIVITAS DI BANJARMASIN - Razak, Mochammad Rahmandi; Aufa, Naimatul; Tharziansyah, Muhammad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Mental Health Center in Banjarmasin is a place designed to cater to the needs of caring and treatment of people’s mental health needs, Facilitating them with sufficient mental health services at an inclusive space for all types of users. This mental health center has the goal of facilitating quality mental health care and needs to those who are in need. This mental health treatment center consists of a ward for psychologists and psychiatrists’ offices, a small pharmacy as well as a dining space that are inclusive to all, including people with disabilities (mobility issues). With the designing method that took on the inclusive approach, It is hoped that the design will be able to create an inclusive healthcare facility for all types of people including those with disabilities to be able to get their treatment, whilst making a new social space to create places to gather.